Anti-Obesity Efficacy Study Of Phaleria Macrocarpa, Hibiscus Sabdariffa, And Moringa Oleifera - Muhamad Ridzwan Krishnamurthy, Zuliana (2021)
Current research aimed to study the in vivo anti-obesity and anti-metabolic syndrome efficacy of Phaleria macrocarpa (P. macrocarpa), Hibiscus sabdariffa (H. sabdariffa) and Moringa oleifera (M. oleifera) through their potential in inhibiting digestive enzyme activities.